Can Anganwadi services strengthening improve the association between maternal and child dietary diversity? Evidence from Project Spotlight implemented in tribal dominated Gadchiroli and Chandrapur districts of Maharashtra, India. - Abhishek Kumar; Sunil Rajpal; Ruby Alambusha; Smriti Sharma; William Joe (PLoS ONE)
Dietary intake is a fundamental determinant of maternal and child nutrition. This paper presents evidence on whether maternal and child dietary diversity can be improved with systemic improvements focused on strengthening training, capacity building, and behavior change communication among frontline workers to encourage improved nutritional practices among mothers and children in the intervention area. The evidence is derived from Project Spotlight intervention that was jointly implemented by Department of Women and Child Development, Government of Maharashtra and Tata Trusts in tribal dominated Gadchiroli and Chandrapur districts in Maharashtra. Based on a pre-post comparison of baseline (2019) and endline (2021) household survey data it is confirmed that there is a significant association between maternal and child dietary diversity in the study area. Notably, dietary diversity in mother-child dyads is marked with a higher consumption of fruits and vegetables as well as eggs and flesh foods. Econometric analysis further reveals that the association between maternal and child dietary diversity has improved after the systems strengthening interventions. The paper concludes that local interventions such as Project Spotlight for strengthening counselling services and coverage by frontline workers and enhancing knowledge and awareness on maternal and child dietary diversity among communities are important for improving maternal and child nutrition.